Explaining a Dark Side: Public Service Motivation, Presenteeism, and Absenteeism. (December 2019) - Jensen, Ulrich Thy; Andersen, Lotte Bøgh; Holten, Ann-Louise
Public service motivation (PSM) has many bright sides, but recent studies also find dark sides, connected to, for instance, higher stress and burnout. However, results on the PSM–absenteeism association are inconclusive. One reason could be that PSM increases presenteeism (going to work even when ill), which in turn increases absenteeism and counteracts—or even exceeds—PSM-based reductions of absenteeism. Based on a three-wave panel study of Danish public and private sector employees, we find a strong positive association between PSM and presenteeism and indications that the PSM–absenteeism link is mediated by presenteeism. The findings suggest that going to work even on days when employees feel ill is a potential dark side of PSM and that it may have long-term consequences for the extent to which employees are absent from their jobs due to sickness. This cautions managers not to expect that high PSM automatically guarantees high performance and low absence.